N2-, O2- and Air-broadened half-widths and line shifts of methyl chloride in the 10 µm region. (March 2021) - Fathallah, O. Ben; Manceron, L.; Dridi, N.; Rotger, M.; Aroui, H.
Highlights: Line-by-line measurements of O2 - and N2 -broadening and shift coefficients in the v6 band of the two isotopes of CH3 Cl have been performed with a high resolution fourier transform spectrometer. Modeling of the rotational dependences of the O2 - and N2 -broadening has been performed using the empirical model of starikov. Air-broadening coefficients are retrieved. Prediction of the O2 - and N2 -broadenings using the robert and bonamy formalism. Abstract: N2 - and O2 -broadening coefficients were measured at room temperature for 2914 ro-vibrational lines of methyl chloride in the region from 920 to 1140 cm −1 corresponding to the ν6 band, using a high-resolution Fourier transform spectrometer and a mono-spectrum non-linear least squares fitting of Voigt profiles. The spectra were recorded at the AILES beamline of the SOLEIL Synchrotron facility at various mixtures of CH3 Cl with N2 or O2 gas. Broadening coefficients were retrieved for the two isotopes of CH3 Cl from which we derived the air-broadenings. The rotational dependences of these coefficients were analyzed and modeled first using an empirical model, which reproduces the measurements within of about 5%. Pressure- induced shifts are also measured for about 375 and 418 transitions for O2 - and N2 -perturbers respectively with no obvious rotational dependence. The average absolute accuracies of the measurements are estimated to be about 7 and 17% for broadening and shift coefficients respectively. Comparisons are performed with previous measurements and next with semi-classical predictions achieved in this work. The entire set of results is given as Supplementary data Table for a use in spectroscopic databases and atmospheric detection.